Long term multi-wavelength analysis of the flat spectrum radio quasar OP 313 - Bartolini, C.; Angelakis, E.; Bissaldi, E.; Cerasole, D.; D’Ammando, F.; Di Venere, L.; Giacchino, F.; Giordano, F.; Giroletti, M.; Lähteenmäki, A.; Lindfors, E.; Myserlis, I.; et al. (Italy, 2026)
The Flat Spectrum Radio Quasar (FSRQ) OP 313 showed intense γ-ray activity from November 2023 to March 2024, as observed by the Fermi Large Area Telescope (Fermi-LAT). We present a multi-wavelength analysis covering 15 years of Fermi-LAT observations, from August 2008 to March 2024. From the γ-ray light-curve study, we identified different periods of high-state activity, called flaring states. These are compared with the data available from other facilities. The long-term multi-wavelength activity of the source was investigated using a wide dataset extending from radio to the γ-ray bands. We investigated the kinematics of the radio jet to probe the mechanisms producing the galaxy’s flaring activity. This approach helps us to understand the mechanisms involved in particle acceleration inside the jet, and how radiation in different wavelengths is connected.
Best communications presented at the 110th National Congress of the Italian Physical Society